PM Emission of Diesel Engines Using Ester-Ethanol-Diesel Blended Fuel - Ahmad Fitri, Yusop; Mohd Hafizil, Mat Yasin; R., Mamat; Abdul Adam, Abdullah; Amir, Aziz (Elsevier Ltd, 2013)
In this study, Palm Oil Methyl Ester (PME) was added to ethanol-biodiesel fuel in order to reduce the emissions. The percentage of ethanol is up to 20% in volume. Thus, the effects of ethanol on particulate matter (PM) components, soluble organic fraction (SOF) and dry soot (DS) using different type of fuel blends were investigated. Using a composite filter, the ester-ethanol-diesel characteristic such as mass concentration in term PM, SOF and DS were analyzed under different engine operating conditions using four cylinder engine. The results show that increasing ethanol in blended fuel will decrease the PM, SOF and DS at low and middle load. In addition, as the load is increased, the PM component such as SOF and DS also increase. Thus, ethanol-biodiesel fuel can reduce the emissions for low and middle load condition.